Synthetic and mechanistic studies of heterocyclic systems - Deane, Philip O'Grady (Rhodes University, Faculty of Science, Department of Chemistry, 1996)
A series of acrylate esters and selected analogues have been reacted with pyridine-2-,pyridine-3-, and pyridine-4-carboxaldehydes in the presence of diazabicyclo[2,2,2]octane (DARCO) to afford a range of Baylis-Hillman products. The pyridine-2-carboxaldehyde-derived products have been acetylated using acetic anhydride and the kinetics of the thermal cyclisation of the acetylated compounds to indolizines was investigated using proton NMR spectroscopy. The first-order kinetics of the cyclisation has been confirmed and the influence of substituents on the first-order rate constant, kâ‚’bs has been examined. The kinetic data has been shown to be consistent with the previously proposed mechanism in which loss of the acetate group is ratedetermining. Each of the cyclisations was also monitored at three different temperatures permitting evaluation of the activation parameters. The Baylis-Hillman products and related acetylated derivatives were treated at room temperature with sodium methylthiolate; the hydroxy precursors were observed to undergo conjugate addition with a degree of diastereocontrol but the acetylated derivatives favoured an apparent SNÂ¹ displacement of the acetate group.
Keywords: Heterocyclic chemistry